Coming into the Cold: China's interests in the Antarctic. - Press, Anthony J.; Bergin, Anthony (Australian Journal of International Affairs, 2022)
China took its first tentative steps into the Antarctic around 1980, travelling South with other nations' Antarctic programs. Australia hosted the first Chinese scientists to travel to East Antarctica to conduct research in the early 1980s. China signed the Antarctic Treaty in 1983 and became a Treaty Consultative Party in 1985. Since its first small forays, China's Antarctic activities have grown considerably: it now has two permanently occupied Antarctic stations, other Antarctic facilities and is currently building a station on in the Ross Sea region. China's Antarctic science program is broad; it has economic activities in the region include fisheries and tourism, and has expressed longer-term interest in resource extraction. In recent years, China has become an assertive participant in Antarctic governance. This paper analyses the geopolitical origins of the Antarctic Treaty, China's growing Antarctic presence, and the implications this has for the region, including the policies and strategies of Australia and key Indo-Pacific partner states in the Antarctic.